Model systems for the study of human norovirus biology. (July 2009) - Vashist, Surender; Bailey, Dalan; Putics, Akos; Goodfellow, Ian
The relative contribution of noroviruses to disease burden on society has only recently been established and they are now established as a major cause of gastroenteritis in the developed world. However, despite the medical relevance of these viruses, an efficient in vitro cell-culture system for human noroviruses has yet to be developed. As a result, much of our knowledge regarding the basic mechanisms of norovirus biology has come from studies using other members of the Caliciviridae family of small positive-stranded RNA viruses. Here, we aim to summarize the recent advances in the field, highlighting how model systems have played a key role in increasing our knowledge of this prevalent pathogen.